Analysis of the Need for the Development of Ethnomathematics-Based Flipbook Media to Improve Understanding of Measurement Concepts in Elementary Schools - Munawwaroh, Dinda Arofahtul; Mariana, Neni; Ekawati , Rooselyna (Papanda Publisher, 2025)
The purpose of this study is to analyze the need for the development of ethnomathematics-based flipbook media to improve students' understanding of measurement materials in grade III of elementary school. The research method used is qualitative with a descriptive approach. Data was collected through in-depth interviews with teachers, participatory observations in the classroom, and documentation studies of the curriculum and teaching materials used. The results of the study show that measurement learning is still dominated by lecture methods and the use of textbooks, so that students have difficulty in understanding abstract concepts. Teachers have also not integrated elements of local culture in learning, although the concept of traditional units of measurement such as cubits and depa is still used in daily life. Therefore, it is necessary to develop ethnomathematics-based digital flipbook media that can present interactive illustrations, visual simulations, and connect measurement concepts with local cultural practices. The conclusion of this study emphasizes that digital flipbooks can be an innovative solution in improving students' understanding of measurement materials while supporting an exploratory approach in the Independent Curriculum. The recommendation of this study is a trial of flipbook media to measure its effectiveness in increasing student engagement and understanding in mathematics learning.